Analisis Efektivias Commuter Line Ticket Vending Machine (C-VIM) terhadap Penanganan Antrian Pembelian Tiket di Stasiun Bekasi - Rahma, Yudhia; Mariam, Iis (Research Center and Case Clearing House PPM School of Management, 2021)
PT KCI innovated the newest service, namely the Commuter Line Ticket Vending Machine (C-VIM). This innovation is intended to answer customer complaints about the time spent queuing for tickets at the counter. C-VIM is a machine of PT KCI service innovation with the aim of parsing the queues that occur at conventional counters. This study aims to determine and analyze how the effectiveness of C-VIM services in handling ticket purchase queues. The research was conducted at Bekasi station as the station with the highest number of passengers in 2019. The study used a quantitative approach by distributing questionnaires to 100 respondents who were C-VIM users. The data analysis technique used in this study is divided into three stages, namely: instrument test, classical assumption test, and hypothesis testing. The instrument test is intended to analyze the validity and reliability tests. The classical assumption test consists of a normality test and a linearity test. Hypothesis testing consists of simple linear regression analysis, simple correlation analysis, coefficient of determination, and significant T test. The results of the data analysis obtained show a significant and positive effect, so it can be said that there is an effect of the effectiveness of C-VIM services in handling ticket purchase queues. at Bekasi Station, therefore, C-VIM is effective to continue to be used in the efforts to improve PT KCI services with the hope that some improvements will occur in the future